(untitled) (World Economics and Finance Bulletin, 2024)
In this article, the main physical qualities and methods of their improvement are studied in the types of wrestling. Also, ideas were given about the methodical correct conduct of wrestling training and the acquisition of necessary physical qualities for wrestlers during training. The results of the research made it possible to determine a number of important issues related to the problem of physical fitness of wrestlers, and at the same time, it was determined that physical qualities are of great importance in ensuring all-round physical fitness of young wrestlers